STUDENTS’ PERCEPTION TOWARD USING SONG LYRICS TO ENRICH VOCABULARY MASTERY (A STUDY CONDUCTED AT POLITEKNIK PELAYARAN SULAWESI UTARA) - Lacoro, Qadria; Pelenkahu, Noldy; Liando, Nihta V. F. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The purpose of this study is to analyze the students’ perceptions toward using songs to enrich students vocabulary mastery.The research used quantitative methods with a descriptive approach and questionnaire as the instrument. The population of this study is students at Politeknik Pelayaran Sulawesi Utara. Moreover, the sample of this study is engineering cadets in the 4th semester at Politeknik Pelayaran Sulawesi Utara consisting of 30 students. In academic years of 2023/2024. The result showed the majority of the participants have positive opinion toward the use of song lyics to enrich vocabulary mastery and can be seen as they picked strongly agree and agree in most of the statements. The positive vibes which English songs spread to the English learning process may be the reason behind that. Researcher finds that songs can be very useful and bring positive impact on learning process. The responses toward 14 items in questionnaire proved that students enjoy to learn English vocabulary through songs.